탄수화물 분해효소 처리에 의한 배 과피와 과심의 항산화 생리활성 증대효과 - 이평화(Pyeong Hwa Lee); 박수연(Su Yeon Park); 장태훈(Tae Hoon Jang); 임순희(Sun-Hee Yim); 남승희(Seung-Hee Nam); 인만진(Man-Jin In); 김동청(Dong Chung Kim); 채희정(Hee Jeong Chae) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
The effects of treatment with various complex carbohydrases such as Pectinex, Celluclast, Viscozyme, and Ultraflo on the physiochemical properties, polyphenol extraction yields and antioxidant activities of pear peel and pear core were investigated. When pear peel and pear core were treated with complex carbohydrases, the soluble solid content of peel increased, whereas it did not change significantly in the case of pear core. When pear peel and pear core were treated with Pectinex, significant improvement of soluble solid content was observed along with the highest extraction yield of reducing sugar content. Total sugar content increased in most of the enzyme treatment groups. In the case of pear peel, the Viscozyme treatment group showed the highest total polyphenol contents, total flavonoid contents, DPPH radical scavenging activity, ABTS radical scavenging activity, and SOD-like activity. When the flesh and core of pear were treated with Celluclast, total polyphenol contents increased. All enzyme treatment groups except for the Ultraflo treatment group showed increases in total flavonoid contents. With regard to pear flesh, the Celluclast group showed the highest DPPH radical scavenging activity. When pear core was treated with the four complex carbohydrases, DPPH radical scavenging activity and ABTS radical scavenging activity did not increase significantly. However, the SOD-like activity of all enzyme treatment groups significantly increased. Consequently, dry matter and soluble solid contents, polyphenol content, and antioxidant activity of pear peel and core could be improved by complex carbohydrase treatment. 배(Pyrus pyrifolia)의 과피와 과심에 복합효소처리 의해 물리화학적 특성 및 기능성에 미치는 영향을 조사하였다. 배의 과피와 과심에 4종의 복합효소를 처리할 경우 과피의 가용성 고형분 함량이 증가하였고 과심은 유의적으로 증가하지 않았다. 과피의 가용성 고형분 함량은 Pectinex로 처리하였을 때 가장 높은 증대효과를 나타냈다. 또한 배의 과피와 과심에 Pectinex로 처리하였을 때 높은 환원당 추출 수율을 얻을 수 있었다. 총당 함량은 대부분의 효소처리군에서 증가하여 효소에 의해 탄수화물이 분해되어 당 함량이 증가하는 것을 확인할 수 있었다. 배의 과피에 Viscozyme으로 처리할 경우 총 폴리페놀 함량, 총 플라보노이드 함량, DPPH radical 소거능, ABTS radical 소거능 및 SOD 유사활성이 가장 높은 증대효과를 보였다. 또한 과심에 Celluclast로 처리할 경우 총 폴리페놀 함량이 증가하였고, 총 플라보노이드 함량은 Ultraflo 처리군을 제외한 나머지 효소처리군에서는 비슷한 양상으로 증가하였다. 또한 과심에 4종의 복합효소처리 시 DPPH radical 소거능과 ABTS radical 소거능은 유의적으로 증가하지 않았고 SOD 유사활성은 모두 증가하였다. 결과적으로 배의 과피와 과심에 탄수화물 분해 복합효소를 처리함으로써 고형분, 환원당 및 항산화 물질의 추출률을 증가시키고 항산화 활성을 향상시킬 수 있음을 확인하였다.